Downhole Telemetry Systems to Monitor Electric Submersible Pumps Parameters in Oil Well - Diego Antonio De Moura Fonseca; Andres Ortiz Salazar; Elmer Rolando Llanos Villarreal; German Alberto Echaiz Espinoza; Alan Cassio Queiroz Bezerra Leite (IEEE Access, 2021)
The electrical submersible pump (ESP) is widely used in the oil industry as an artificial lift method in deep wells, and its primary application of ESP is to increase the oil flow rate. Information such as the pump intake and discharge pressure, the oil reservoir and motor winding temperature, etc., provide critical data necessary to ensure proper ESP system operation and optimize production. In this article, an ESP downhole parameter monitoring system is proposed. Potentiometers are used to generates analog signals, emulating the analog sensors. The information is sent up to the surface based on the current loop through the same power cable by DC signals overlapping to AC signals in the proposed design. The article details the construction of the communication protocol and electronic circuits used in telemetry. The tests were carried out in an oil-producing company to validate the proposed telemetry system's reliability and accuracy. The good results of the robust design demonstrated it to be a promising downhole sensor for industrial applications.